Teachers' Experience of Teaching and Online Learning Via WhatsApp as a Combination of Interactive English Learning media in the Covid-19 Pandemic Era of UNU Lab Elementary School Students in Blitar - Bagus Waluyo; Oikurema Purwati (Journal of Development Research, 2020)
English learning in elementary schools should be engaging, interactive and fun so that students have an interest and motivation for learning especially in the current Covid-19 pandemic, but in reality, the learning patterns in SD Lab Blitar UNU still do not apply English learning patterns that are interactive and fun online because teachers have not affected the learning model that suits students' needs. They find it difficult to determine the right online media as a learning medium due to locations that do not support using the full online facility. The purpose of this study is that the authors intend to provide solutions in formulating exciting and interactive patterns of English teaching to all teachers and students during the co-19 pandemic under online learning conditions. The author uses a qualitative approach through the case study application and applies self-selection to select audiences and conduct online interviews to retrieve all data in the completeness of the study. The results revealed that Teachers' Experience of Teaching and Online Learning Via WhatsApp could create Interactive English Learning in the Covid-19 Pandemic Era, and the Combination can attract students' interest in learning online.